Factors influencing the practice of breast self-examination among teenage girls in Salatiga City, Indonesia - Tauho, Kristiani Desimina; Dary, Dary; Anshebo, Abebe Alemu; Ondowapo, Magried Paulina (International Journal of Public Health Science (IJPHS), 2025)
Breast cancer is the second leading cause of cancer-related mortality among women in Indonesia. Early detection improves survival, yet many adolescent girls do not practice breast self-examination (BSE). Evidence on personal barriers among young women remains limited. To analyze knowledge, perceived susceptibility, and barriers to BSE practice among late adolescents in Salatiga, Central Java. A cross-sectional study was conducted in February 2023 among 67 female students aged 18-21 years living in a university dormitory. Data were collected using a self-administered questionnaire based on the Health Belief Model and analyzed with descriptive statistics and logistic regression. Most respondents (70.1%) had received BSE information, mainly from social media (35.8%) and school (32.8%). Barriers included perceiving BSE as unimportant (37.3%), lack of knowledge (35.8%), belief that it was unnecessary without illness (38.8%), and feeling too young (20.9%). Logistic regression identified four predictors of non-practice: lack of knowledge (OR = 0.003, 95% CI: 0.000-0.243, p = 0.010), belief BSE is only needed with symptoms (OR = 0.022, 95% CI: 0.002-0.312, p = 0.005), lack of privacy (OR = 0.026, 95% CI: 0.001-0.946, p = 0.046), and time constraints (OR = 0.064, 95% CI: 0.006-0.701, p = 0.024). Misconceptions, limited knowledge, and social constraints were the main barriers to BSE practice among adolescent girls. Addressing these requires school-based programs, integration of BSE into reproductive health curricula, and community campaigns, while nursing practice should focus on enhancing self-efficacy and normalizing BSE.